2021
DOI: 10.3390/sym13091683
|View full text |Cite
|
Sign up to set email alerts
|

Sigma Identification Protocol Construction Based on MPF

Abstract: A new sigma identification protocol (SIP) based on matrix power function (MPF) defined over the modified medial platform semigroup and power near-semiring is proposed. It is proved that MPF SIP is resistant against direct and eavesdropping attacks. Our security proof relies on the assumption that MPF defined in the paper is a candidate for one-way function (OWF). Therefore, the corresponding MPF problem is reckoned to be a difficult one. This conjecture is based on the results demonstrated in our previous stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…There, MPF was defined over the non-commuting medial semigroup, which by nature, is almost commuting. This property implies that the main MPF identity necessary to construct a SIP is valid together with the two-sided associativity of MPF [9]. In that paper, we have shown that the proposed SIP is resistant to passive impersonation attacks by demonstrating that our protocol is a special honest Verifier zero knowledge.…”
Section: Response Challengementioning
confidence: 72%
See 2 more Smart Citations
“…There, MPF was defined over the non-commuting medial semigroup, which by nature, is almost commuting. This property implies that the main MPF identity necessary to construct a SIP is valid together with the two-sided associativity of MPF [9]. In that paper, we have shown that the proposed SIP is resistant to passive impersonation attacks by demonstrating that our protocol is a special honest Verifier zero knowledge.…”
Section: Response Challengementioning
confidence: 72%
“…Our previous attempt to construct a SIP using MPF defined over a non-commuting semigroup was presented in [9]. There, MPF was defined over the non-commuting medial semigroup, which by nature, is almost commuting.…”
Section: Response Challengementioning
confidence: 99%
See 1 more Smart Citation